Whistle variability of the Mediterranean short beak common dolphin. (23rd October 2019) - Azzolin, Marta; Gannier, Alexandre; Papale, Elena; Buscaino, Giuseppa; Mussi, Barbara; Ardizzone, Giandomenico; Giacoma, Cristina; Pace, Daniela Silvia
Abstract: The short‐beaked common dolphin is a highly vocal species, with a wide distribution in all oceans, including the Mediterranean and the Black Seas. In the Mediterranean Sea, the short‐beaked common dolphin inhabits both pelagic and neritic waters. Osteological collections and the literature show that short‐beaked common dolphins were widespread and abundant in much of the Mediterranean Sea until the late 1960s. During recent decades the species has declined in the whole basin, and, in 2003, it was listed as Endangered in the IUCN Red List. Genetic studies strongly suggest that the Mediterranean and the Eastern North Atlantic populations are isolated from each other. Genetic differentiation within the Mediterranean Sea, between the Eastern Mediterranean (Ionian Sea) and Western Mediterranean populations, is also reported. The aim of this study was to investigate the geographical variation in the characteristics of whistles of free‐ranging short‐beaked common dolphins living in the Mediterranean Sea, and to evaluate if whistle acoustic structure is the result of adaptation to local environment characteristics or of a possible genetic diversification. Recordings were collected from 1994 to 2012 throughout the basin, employing multiple platforms. Twenty‐six independent acoustic detections were made, and 704 whistles were extracted and considered for statistical analysis. Whistle analysis enabled the identification of distinct geographical units of short‐beaked common dolphin within the Mediterranean Sea. Genetic isolation is probably the major cause of the geographic variance of the Mediterranean short‐beaked common dolphin whistle structure, which may reflect some evolutionary adaptations to particular ecological conditions or may be the by‐product of morphological evolution. The results of the present study show that intra‐Mediterranean variability of whistle structure reflects the path of genetic studies, highlighting the possible use of acoustic data in combination with other sources of data (genetic, morphological, etc.) to identify geographic areas where discrete management units occur.